(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Health anthropology is the discipline that is responsible for understanding the expressions and narratives that make up feeling, suffering and expressing, about pathological symptoms, and how these are explained from the worldview of a certain context, as well as its methods and instruments to cure and prevent disease. It is from such concerns that I start towards the systematization and compilation of research that has anthropology as a reference center, transcending the field of mental health, from psychology, psychiatry and sociology, agglomerating and stressing on the positions and reflections generated by the authors. It is in this tension that feeling and expressing are situated, as two core axes to understand mental illness, understanding that the condition has variances and different nuances, according to the institutions, cultural, semiotic and linguistic dynamics, where the patient is immersed.